Two Sided Markets: The Case of The Waterbed Effect in OECD Mobile Telecommunications Markets - Mikail Kar (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
Efforts to develop appropriate policies and accurate strategies through the most accurate analyzes highlight the examination of two-sided markets, which differ significantly from one-sided markets. In this study, mobile telecommunications market which has a special place in two-sided market analysis will be studied. In mobile telecommunications market, it is suggested that a reduction in mobile interconnection rates for the interconnection service will show the waterbed effect, resulting in an increase in mobile communication prices that the end user faces in the market. In this context, an empirical analysis was made by Common Correlated Effects Mean Group (CCEMG) estimator using the 41 quarter period data of 21 OECD countries between 2005 and 2015, and the effect of mobile interconnection rates, income and quantity were estimated in determining the mobile communication prices. According to the results, the waterbed effect in mobile telecommunications markets could not be determined in the period analyzed for the related country group and mobile interconnection rates acted as a cost factor and changed the prices in the same direction.  The coefficient of income variable was positive and the expectation that the increase in income would increase the price was met.  The explanatory variable coefficients of the number of subscribers and the penetration rate representing the quantity were negative and they were evaluated to behave in accordance with economic expectations and two-sided market characteristics.